Back Cover: Biocompatible SuFEx Click Chemistry: Thionyl Tetrafluoride (SOF4)‐Derived Connective Hubs for Bioconjugation to DNA and Proteins (Angew. Chem. Int. Ed. 24/2019). Issue 24 (22nd May 2019) - Liu, Feng; Wang, Hua; Li, Suhua; Bare, Grant A. L.; Chen, Xuemin; Wang, Chu; Moses, John E.; Wu, Peng; Sharpless, K. Barry
Abstract : SuFEx goes biology New biocompatible SOF4 ‐based SuFEx reactions operating at low concentration in aqueous solution under mild pH and temperature conditions provide access to asymmetric and trisubstituted products at the sulfur(VI) center with versatile S−N and S−O connectivity. The SuFEx bioconjugation of iminosulfur oxydifluorides to either BSA protein or to single‐stranded DNA is demonstrated. Details can be found in the Communication by K. B. Sharpless et al. on page 8029.